Montessori from the start: The child at home, from birth to age three - Lillard, Paula Polk; Jessen, Lynn Lillard (New York, 2003)
This informed, careful. and intelligent response to the unfolding of personality will peak parents' interest as they learn how to establish healthy, enjoyable, and sustaining relationships with their children. A must for parents-to-be, nannies, and care-givers.
Keywords: Education, Preschool- Parent Participation; Child Development; Montessori Method of Education